Sacred heritage in Japan - Rots, Aike P.; Teeuwen, Mark (Abingdon, Oxon ; New York : Routledge, 2021)
"Sacred Heritage in Japan is the first volume to explicitly address the topics of Japanese religion and heritage preservation in connection with each other. Examining what happens when places of worship, such as Buddhist temples, Shinto shrines, or Christian churches, and religious practices are rebranded as national culture, the book considers the impact of being designated tangible or intangible cultural properties and, more recently, as UNESCO World or Intangible Heritage. Drawing on primary ethnographic and historical research, the contributions to this volume show the variety of ways in which different actors have contributed to, negotiated, and at times resisted the transformation of religious traditions into heritage. Considering the conflicts that emerge about questions of signification and authority during these processes of transformation, the book provides important new perspectives on the local implications of UNESCO listings in the Japanese context and showcases the diversity of "sacred heritage" in present-day Japan. Combining perspectives from heritage studies, Japanese studies, religious studies, history and social anthropology, the volume will be of interest to scholars and students who want to learn more about the diversity of local responses to heritage conservation in non-Western societies. It will also be of interest to scholars and students engaged in the study of Japanese religion, society, or cultural policies"--
Heritage-Making and the Transformation of Religion in Modern Japan / Mark Teeuwen and Aike P. Rots -- World Cultural Heritage and Women's Exclusion from Sacred Sites in Japan / Lindsey E. DeWitt -- Omissions, Stratagems, and Dissent: The Shikoku Pilgrimage and the Problems of Applying for World Heritage Status / Ian Reader.
Includes bibliographical references and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Cultural property -- Protection -- Japan -- Religious aspects; Historic preservation -- Social aspects -- Japan; Religion and culture -- Japan